Caracterización molecular de poblaciones venezolanas de Sigmodon hirsutus(Rodentia: Cricetidae) - Lessmann, Janeth (2011)
Recent phylogenetic studies based on cytochrome b gene sequence, have determined that the spe-cies historically known as Sigmodon hispidus (Rodentia) from South America comprises a species S. hirsutus of paraphyletic origin. The aim of this study was to test the hypothesis that populations from Venezuela, represent the sensu strict form, ancestral haplotypes, and monophyletic subspecies. For this, 12 individual sequences from three localities of different biogeographic regions in Venezuela were evaluated and sequenced based on cyto b. Additionally, the sequences were used to develop a cladistic analysis and genetic distance calculations, and to compare this information with two individual sequences of Sigmodon specimens available in Genbank. Phylogenetic analyses show that the three populations of S. hirsutus of Venezuela form an ancestral and monophyletic subclade supported by high bootstrap values and significant genetic distance between subclade within the S. hirsutus. Besides, the existence of two lineages suggests two subspecies, S. hirsutus hirsutus from Venezuela, and S. hirsutusmexicanus from Mexico-Central America, but, both species need formal description.